2018
DOI: 10.1080/00224499.2018.1437116
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype Deduction About Bisexual Women

Abstract: Bisexuals are an invisible sexual minority. However, at the same time, bisexuals are stereotypically associated with confusion and promiscuity. Stereotype learning theories suggest that individuals who are unfamiliar with a social group are less likely to have stereotypical beliefs about its members. In contrast, it has been recently hypothesized that stereotypes about bisexuality are not necessarily learned but rather deduced based on common conceptualizations of sexuality. Because stereotypes are suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 44 publications
2
39
1
Order By: Relevance
“…Previous research into stereotypes about bisexual people have found a lack of knowledge among heterosexual individuals about traits associated with bisexual women and men (Zivony and Lobel, 2014), while homosexual and bisexual individuals report stereotypes closer to those about homosexual groups (Burke and LaFrance, 2016a,b). The need for further study into determining factors for stereotype content in relation to bisexual groups is not limited to perceiver sexual orientation, but also includes salience of the assumed gender of sexual partners (Zivony and Saguy, 2018) and the impact of essentialist views on sexuality (Hubbard and de Visser, 2015). This can provide further information on how gender is given meaning by a perceiver depending on the interplay of gender, sexual orientation, gender of partner, and perceiver attitudes.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Previous research into stereotypes about bisexual people have found a lack of knowledge among heterosexual individuals about traits associated with bisexual women and men (Zivony and Lobel, 2014), while homosexual and bisexual individuals report stereotypes closer to those about homosexual groups (Burke and LaFrance, 2016a,b). The need for further study into determining factors for stereotype content in relation to bisexual groups is not limited to perceiver sexual orientation, but also includes salience of the assumed gender of sexual partners (Zivony and Saguy, 2018) and the impact of essentialist views on sexuality (Hubbard and de Visser, 2015). This can provide further information on how gender is given meaning by a perceiver depending on the interplay of gender, sexual orientation, gender of partner, and perceiver attitudes.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Conversely, bisexuality is publicly invisible (Zivony & Saguy, 2018). Public awareness of bisexuality and focus on bisexual-specific issues is limited, including within broader queer communities (Gurevich et al, 2007;Zivony & Saguy, 2018).…”
Section: Visible Bodies and Invisible Sexualitiesmentioning
confidence: 99%
“…Conversely, bisexuality is publicly invisible (Zivony & Saguy, 2018). Public awareness of bisexuality and focus on bisexual-specific issues is limited, including within broader queer communities (Gurevich et al, 2007;Zivony & Saguy, 2018). Social and academic movements for queer rights and inclusion have excluded bisexual people (see Rothblum, 2020;Weier, 2020).…”
Section: Visible Bodies and Invisible Sexualitiesmentioning
confidence: 99%
See 2 more Smart Citations